Dolgotrajna 3D simulacija transporta in disperzije živega srebra v Tržaškem zalivu - Žagar, Dušan (Acta hydrotechnica, 2001)
An existing 3D mathematical model PCFLOW3D was upgraded to simulate long-term transport and the dispersion of mercury in its dissolved and particulate form. Hydrodynamics due to wind, tidal forcing and river inflow momentum can be simulated, and stratified conditions can be taken into account. Data on temperature and salinity fields and winds in the Gulf of Trieste, Soča River discharges, suspended sediment concentractions and temperature were collected and interpreted. These data, together with measurements of mercury concentrations in the water, suspended sediment, bottom sediment and pore waters in the Soča river and the Gulf of Trieste are used as input for the model. A scenario for long-term simulations on the basis of seasonally averaged parameters and a few shorter inserts of strong wind and high discharges of the Soča river was developed as a substitute for simulations based on annual averaged input data. Measurements and observation data from 1995-1997 were applied to verify and calibrate the PCFLOW3D model. Although some complex mercury transformation processes are not well known and were therefore not taken into account in the simulations, an acceptable qualitative agreement of results and measurements was achieved. Whenever a quantitative comparison was possible, an accordance of measured and computed results within a factor of two was attained.
Keywords: 3D model; Gulf of Trieste; matematično modeliranje; mathematical modelling; mercury; Tržaški zaliv; živo srebro